The precise value of commutativity degree in some finite groups - Moradipour, Kayvan (Ibnu Sina Institute for Fundamental Science Studies, Universiti Teknologi Malaysia, 2012)
The commutativity degree of a finite group G, denoted by P(G), is the probability that a selected chosen pair of elements of G commute. The object of this paper is to compute a precise value of commutativity degree of some finite metacyclic p-groups of class at least 3. In particular, we describe the commutativity degree of these groups in split and non-split case.